2018
DOI: 10.1101/273417
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Compartmentalized RNA catalysis in membrane - free coacervate protocells

Abstract: Phase separation of mixtures of oppositely charged polymers provides a simple and direct route to compartmentalization via coacervation, which may have been important for driving primitive reactions as part of the RNA world hypothesis. However, to date, RNA catalysis has not been reconciled with coacervation. Here we demonstrate that RNA catalysis is viable within coacervate microdroplets and further show that these membrane-free droplets can selectively retain longer length RNAs while permitting transfer of l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…Recently, it had been suggested that phase separated liquid-like compartments composted of oppositely charged molecules, called coacervates, could be ideal seeds for prebiotic life [41]. In particular, RNA catalysis is viable within these coacervate droplets and they even provide a mechanism for length selection of RNA [42]. In all these systems, the droplet material does not participate in the chemical reaction.…”
mentioning
confidence: 99%
“…Recently, it had been suggested that phase separated liquid-like compartments composted of oppositely charged molecules, called coacervates, could be ideal seeds for prebiotic life [41]. In particular, RNA catalysis is viable within these coacervate droplets and they even provide a mechanism for length selection of RNA [42]. In all these systems, the droplet material does not participate in the chemical reaction.…”
mentioning
confidence: 99%
“…5,87 If really formed, such coacervate droplets (usually micrometre-sized) did not have a membrane but were membrane-less compartments. Depending on the type of coacervate, i.e., the molecular composition, it was shown in laboratory experiments that coacervates can concentrate prebiotically relevant molecules, such as amino acids, peptides, lipids, nucleotides, and RNA, which encourage RNA polymerization and ribozyme catalytic activity, 88,89 thereby promoting metabolic reactions. 90,91 In addition, fatty acids encapsulated in coacervates show a transition from membrane-free compartmentalisation to membranebound compartmentalisation.…”
Section: Approaches To Living Systemsmentioning
confidence: 99%
“…Koazervate sind kugelförmige Molekülaggregate, die sich durch elektrostatische Assoziation von entgegengesetzt geladenen Makroionen bilden und schon lange mit dem Ursprung des Lebens in Verbindung gebracht werden [7]. Kürzlich konnten wir zusammen mit zwei anderen Forschungsgruppen tatsächlich nachweisen, dass Ribozyme spontan von Koazervaten aufgenommen werden, sich in ihnen konzentrieren und dort auch katalytisch aktiv sind [8].…”
Section: Synthetische Biologieunclassified